Land administration for land surveyors - A. Kadir, Abd. Majid; Desa, Ghazali (Fakulti Kejuruteraan Sains Dan Geoinformasi, 2003)
This book contains several chapters, table of contents part i: general background the concept of tend and the dynamic humankind-land relationship the land administration response part ii: advent of land administration lei>d registration the cadastre concept cadastral surveying and mapping land administration best practices selected additional reading part 111; land administration systems in Malaysia land administration system in Peninsular Malaysia peninsular malaysia cadastral system fn digital eriyirqnrrjent institutional arrangement " " ' :j " land use and planning related policies in Peninsular Malaysia land administration system in Sabah :v land administration system in Sarawak ' l selected additional reading part iv: international initiatives un-fig bogor declaration bathurst declaration fig cadastre 2014 selected additional reading part v: technology digital cadastral databases: case study - peninsular Malaysia/australia coordinated cadastral system: case study - Peninsular Malaysia computerised land registration system: case study - Peninsular Malaysia GDM2000 - Malaysia selected additional reading part vi: spatial data infrastructure (sdi) sdi: concept and hierarchy sdi: decision support system selected additional reading part vji: future trends and issues re-engineering land administration systems benchmarking tand administration systems selected additional reading.